Peran Zakat dalam Mewujudkan Kesejahteraan Umat: Perspektif Maqasid Syariah dan Implementasinya di Palembang - Radhiatul Umami; Mujiadi Mujiadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the conformity of zakat implementation with the principles of Maqasid Syariah in promoting the welfare of the Muslim community in Palembang. Zakat is positioned as an instrument for wealth distribution and social empowerment within the Islamic economic system. This research employs a qualitative approach using a descriptive–analytical method based on library research and secondary data analysis, including classical and contemporary literature on Maqasid Syariah as well as official reports from zakat management institutions. The results indicate that the implementation of zakat in Palembang generally aligns with the primary objectives of Maqasid Syariah, particularly in the aspect of protection of life (ḥifẓ al-nafs) through humanitarian programs and health services, as well as protection of religion (ḥifẓ al-dīn) through support for religious education and spiritual development. Meanwhile, the aspects of protection of intellect (ḥifẓ al-ʿaql) and protection of wealth (ḥifẓ al-māl) have been implemented through educational assistance and economic empowerment programs, although they still face sustainability challenges. The protection of lineage (ḥifẓ al-nasl) is reflected implicitly through health initiatives and family assistance programs. This study concludes that optimizing zakat requires more integrated management that is oriented toward fulfilling all dimensions of Maqasid Syariah.